Big Mac Trademark Dispute in the European Union Between Mcdonald's And Supermac's - Iswardhana, Muhammad Ridha (Law and Economics, 2026)
The dispute between the American fast food giant McDonald's and the Irish fast food chain Supermac’s over the Big Mac trademark in the European Union highlights important issues in trademark law and market protection. The conflict began in 2015 when Supermac's applied to register its name as a trademark for restaurant services in Europe, but McDonald's opposed the registration, claiming that the name "Supermac's" was too similar to its iconic "Big Mac." In 2017, Supermac's requested the cancellation of the Big Mac trademark, arguing that McDonald's had not used it in relation to specific products and services in the EU for five consecutive years. The European Union Intellectual Property Office (EUIPO) ruled in favor of Supermac’s, canceling McDonald’s Big Mac trademark, citing failure to prove genuine use of the trademark. This research aims to analyze the impact of this decision on the protection of McDonald's trademark in the EU. Using a qualitative approach and trademark protection concept focusing on identity and distinctiveness, the study finds that the cancellation of the Big Mac trademark could disrupt McDonald's market share in the EU, leading to consumer confusion and a loss of trust in the brand.